Flume investigation of landslide granular debris and water runup mechanisms. Issue 1 (7th January 2015) - ,; ,; Ng, C. W. W.; ,
Abstract : The heights of rigid debris flow barriers are designed to provide adequate retention and prevent debris from over-spilling. Designers need to predict potential runup height against a vertical wall to account for potential over-spilling. Experimental investigations of debris flow runup have previously been conducted using dry sand. A 5 m long rectangular flume was used to conduct runup experiments using both dry sand and water, separately. A combination of high-speed imagery, photoconductive sensors and laser sensors was used to study runup along the vertical face of a rigid barrier. The effect of Froude number (Fr) on runup was  examined by varying the channel inclination. Commonly adopted energy and momentum approaches for predicting runup were compared with experimental results. The results reveal that runup  mechanisms are dependent on approach Fr conditions and whether the flow medium is frictional in nature. For water, subcritical flows  did not exhibit significant runup (reflective wave mechanism), whereas supercritical flows led to a vertical jet runup mechanism. Supercritical sand flow resulted in a pile-up mechanism instead of distinct runup.